Controlling interest and firm efficiency: Comparing family- and nonfamily-controlled Taiwanese cultural and creative industry firms - Kweh, Qian Long; Ting, Irene Wei Kiong; Lu, Wen-Min; Le, Hanh Thi My (John Wiley & Sons, Ltd., 2024)
The study evaluates the efficiencies of Taiwanese cultural and creative firms, comparing family and nonfamily firms. A novel chance-constrained network data envelopment analysis model measured efficiency from 2005 to 2020. Key findings include the following: (1) Nonfamily firms are more efficient than family-controlled firms, and (2) a nonlinear relationship between controlling shareholdings and efficiency is present only in family-controlled firms. This study offers key insights for policymakers, management, highlighting the importance of R&D investment for enhancing firm efficiency, the strategic role of family control in early-stage efficiency improvements through R&D and the need for investors to adopt tailored strategies to optimize efficiency.